Oxidation behaviour of FeCo-2V - Lam, Zanni Xing Chen (Nanyang Technological University, 2022)
FeCo-2V offers a series of excellent mechanical and magnetic properties that makes it highly suitable for electrical machines for aircraft. However, there is little information on the oxidation behaviours of this alloy. In this study, we investigated the oxidation behaviours of FeCo-2V alloy at different temperatures and time. The samples had undergone thermal oxidation at 250, 400 and 550℃ for a duration of 100h, 225h, 400h and 625h respectively. We aimed to analyse the growth rate and the compositions of the oxides formed by observing the weight change and cross-sections of the sample with XRD and SEM-EDS. The XRD and SEM results suggested the formation of an outer oxide layer rich in iron and an inner oxide layer rich in cobalt and vanadium.